Processos comunicacionais na mídia digital: estratégias sociotécnicas de visibilidade e legitimidade nos blogs corporativos - Lasta, Elisangela (2012)
This dissertation has as its theme the communication processes developed organizations in the digital media / corporate blog, which is enclosed in the examination of socio-technical strategies of visibility and legitimacy undertaken in 16 blogs the corporate Medium-Large Business and Large Business of the blogsphere Brazilian. The overall objective is to develop an array of strategies for socio-technical visibility and legitimacy for corporate blogs with the intention of responding to problem: what strategies sociotechnical practiced organizations in promoting corporate blogs that search visibility and legitimacy '. The methodology uses empirical research proposal mediated computer (Johnson, 2010), from two main methods for research qualitative: the hidden field observation and non-participatory and triangulation methodological techniques. The theoretical approach and methodology developed in this research focused on the finding that 68.75% of companies are conspicuous by their field of study sociotechnical strategy of visibility positioned at the level of relationship intermediate and 75% by sociotechnical strategy of legitimacy positioning also returned to the relationship and intermediate level. The positioning of relationship besides having preferably is at intermediate level and therefore absorbed in the socio-technical strategies of visibility and legitimacy in more than half corporate blogs the field of study.